A relational approach to street gangs - Papachristos, Andrew V. (The Oxford handbook of gangs and society, 2024)
The gang world is built not through individual actions alone, but by larger constellations of relationships and social networks between and within groups, their members and associates, and the relationship between gangs and their social environs. This chapter advances a relational understanding of gangs and gang behaviors that extends the group process perspective by more deeply tying gang research to relational thinking and social network theory. A relational or network-oriented approach centers the group nature of gangs but, at the same time, problematizes it by showing the complexities of boundaries and patterns of influence within and between groups. The objective is to measure - rather than assume - structure, which urges researchers to focus on analytically constructing and measuring “the gang” in ways that capture how these complex, evolving, and overlapping social entities are consequential for individual and collective behaviors. To spur future research, this chapter also reviews qualitative and quantitative data and methods that can be used to conduct studies of gangs via a relational perspective.